Patients' ability to treat anaphylaxis using adrenaline autoinjectors: a randomized controlled trial. Issue 7 (16th April 2015) - Umasunthar, T.; Procktor, A.; Hodes, M.; Smith, J. G.; Gore, C.; Cox, H. E.; Marrs, T.; Hanna, H.; Phillips, K.; Pinto, C.; Turner, P. J.; Warner, J. O.; et al.
Abstract Background Previous work has shown patients commonly misuse adrenaline autoinjectors (AAI). It is unclear whether this is due to inadequate training, or poor device design. We undertook a prospective randomized controlled trial to evaluate ability to administer adrenaline using different AAI devices. Methods We allocated mothers of food‐allergic children prescribed an AAI for the first time to Anapen or EpiPen using a computer‐generated randomization list, with optimal training according to manufacturer's instructions. After one year, participants were randomly allocated a new device (EpiPen, Anapen, new EpiPen, JEXT or Auvi‐Q), without device‐specific training. We assessed ability to deliver adrenaline using their AAI in a simulated anaphylaxis scenario six weeks and one year after initial training, and following device switch. Primary outcome was successful adrenaline administration at six weeks, assessed by an independent expert. Secondary outcomes were success at one year, success after switching device, and adverse events. Results We randomized 158 participants. At six weeks, 30 of 71 (42%) participants allocated to Anapen and 31 of 73 (43%) participants allocated to EpiPen were successful – RR 1.00 (95% CI 0.68–1.46). Success rates at one year were also similar, but digital injection was more common at one year with EpiPen (8/59, 14%) than Anapen (0/51, 0%, P = 0.007). When switched to a new device without specific training, success rates were higher with Auvi‐Q (26/28, 93%) than other devices (39/80, 49%; P < 0.001). Conclusions AAI device design is a major determinant of successful adrenaline administration. Success rates were low with several devices, but were high using the audio‐prompt device Auvi‐Q.